Appraisal of radiation dose with 64-slice computed tomography perfusion in lung cancer patients with special reference to SSDE: An initial experience in a tertiary care hospital - Bhatt, Shuchi; Srivastava, Ajai K; Meena, Neha; Thakur, Shweta (Indian Journal of Radiology and Imaging, 2017)
Context: Computed tomography perfusion (CTP) is an important functional tool for lung cancer. It is expected to deliver high radiation dose, making its accurate estimation important. Size-specific dose estimate (SSDE) is a new dose metric, which includes the scanner output as well as the patient size. Aims: To determine radiation dose [CT dose index (CTDIvol), dose length product (DLP), effective dose (ED), and SSDE] for CTP in lung cancer and the correlation of CTDIvol, DLP, and SSDE with effective diameter and SSDE with weight, body mass index (BMI), and the scan length. Settings and Design: Cross-sectional study in the Department of Radio-diagnosis from October 2015 to March 2016. Patients and Methods: Due ethical approval and informed consent was taken. Thirty consecutive adult patients of lung cancer undergoing CTP study were included; various radiation dose parameters were determined and presented as mean ± SD. Statistical Analysis Used: Paired Student's t-test and Pearson correlation using Statistical Package for the Social Sciences, Version 16. Results: Mean radiation dose was CTDIvol = 270.138 ± 1.627 mGy, DLP = 681 ± 53.496 mGy.cm, ED = 12.501 ± 0.923 mSv, SSDE = 388.90 ± 81.27 mGy. The CTDIvol and DLP had significant positive correlation (r = 0.556, P= 0.000 and r = 0.522, P= 0.003, respectively) with effective diameter. SSDE had strong negative correlation (r = −0.997, P= 0.000) with effective diameter, significant negative correlation with the BMI (r = −0.889; P= 0.000) and weight (r= −0.910, P= 0.000) of patients. Scan length was not significantly correlated in SSDE (r = −0.012, P= 0.951). Conclusions: Smaller sized patients had greater SSDE.
Keywords: Lung cancer; multidetector computed tomography; patient safety; perfusion imaging; radiometry